Primitive neuroectodermal tumor of the esophagus with metastasis in the pineal gland - Blas Jhon, Leonardo; Sánchez-Fayos, Paloma; Martín Relloso, Maria Jesus; Calero Barón, Daniel; Porres Cubero, Juan Carlos (Endoscopy International Open, 2019)
Primitive neuroectodermal tumors (PNET) are very rare tumors that belong to a family of malignant neoplasms of tiny round cells which are derived from the neural crest. This report discusses a rare case of an adult woman with esophageal PNET, confirmed by immunohistochemistry, that presented with metastasis to the pineal gland. To our knowledge, this is the first case report of a PNET with these features. Despite surgery and chemotherapeutic treatment, our case has shown disease progression.